Behaviors of Domestic Tourists in the Special Economic Zone in Nakhon Phanom Province - Mooncome, Orathai; Na Thalang, Chawalee (Dusit Thani College Journal, 2020)
The purpose of this study were 1) to study the behaviors of tourists in the special economic zone in Nakhon Phanom Province; and 2) to study the relationship between personal factors and tourist behaviors in the special economic zone in Nakhon Phanom province. This research was quantitative research, involving the collection of data through questionnaires with 400 participants. The analysis method is descriptive statistics such as frequency, percentage, and a chi-squared test with a significance of 0.05. The results found that the behaviors of tourists in the special economic zone in Nakhon Phanom province were as follows: most tourists were traveling in this area for the first time, were traveling with families and relatives, were traveling during the weekend, were using a private car to travel, and spent on average 2,001-4,000 THB on their traveling expenses. What attracts tourists to the special economic zone in Nakhon Phanom province is the variety of tourism resources in this area. Tourists are interested in traveling in an area with Buddhist sites (i.e. religious and cultural tourism), and in paying respect to the relics of Buddha in the pagoda at Phra Thad and to other sacred objects in temples such as Maha-That Temple and Ao-Kad Sri Bua Ban Temple as well as other temples in this area. According to statistics, there were 905,501 domestic tourists in the special economic zone in Nakhon Phanom Province province in 2016. Tourists visited because Nakhon Phanom has many tourism resources connected to history and culture that can attract tourists, such as the Thai-Laos Friendship Village, Ban Na-chok, the Nong Yad sub-district, and the Muang district. In addition, Nakhon Phanom is a small scenic city which is not too overcrowded, livable, and suitable for relaxation. Furthermore, Nakhon Phanom is connected by road to Thailand, Laos, Vietnam, and Southern China. The third Thai–Lao Friendship Bridge (Nakhon Phanom-Khammouane) is important as an economic bridge linking Thailand to the Asian community. The results of the chi-squared test identified that gender is related with the number of visits, the mode of travel, the kind of vehicle used for traveling, and the reason for choosing the tourist sites. There is no relationship between age and tourist behavior or needs. The level of education is connected with the number of visits, the mode of travel, the time of year in which travel occurs, the vehicle used for travel, expenditure on travel, the attractions at tourist sites and the style of tourism that tourists are interested in, and the reasons for choosing tourist sites. Career is connected with the number of visits, mode of travel, vehicle used for travel, expenditure on travel, and the reasons for choosing tourist sites. Average monthly income is connected with the mode of travel, the time of year in which travel occurs, the kind of vehicle used for travel, and expenditure on travel at a significance of 0.05